Improving efficiency in training on sewing ao dai with supporting tools including new assembling process and instructional videos - Phung , Thi Bich Dung (Journal of Technical Education Science, 2021)
In reality, practice teaching shows that the number of students completing the Ao Dai products does not meet the requirements on time and quality with a high rate up to 60%. One of the main reasons is that the currently sewing process still has many limitations, especially in large groups, most students do not observe clearly and carefully the instructor’s sample manipulation. This article presents research results on building supporting tools including a new sewing process and instructional videos to improve Ao Dai sewing efficiency. Experimental teaching results showed that the percentage of students who completed products on time and requirements in terms of quality increased by more than 40%. Most students satisfied with the quality of the supporting tools which help to not only improve their knowledge but also practice sewing skills.